N-Heterocyclic carbene–palladium(II)-1-methylimidazole complex catalyzed Mizoroki–Heck reaction of aryl chlorides with styrenes - Gao, Ting-Ting; Jin, Ai-Ping; Shao, Li-Xiong (Beilstein Journal of Organic Chemistry, 2012)
A well-defined N-heterocyclic carbene–palladium(II)-1-methylimidazole [NHC-Pd(II)-Im] complex 1 was found to be an effective catalyst for the Mizoroki–Heck reaction of a variety of aryl chlorides with styrenes. Both activated and deactivated aryl chlorides work well to give the corresponding coupling products in good to excellent yields by using tetrabutylammonium bromide (TBAB) as the ionic liquid.
Keywords: aryl chloride; Mizoroki–Heck reaction; N-heterocyclic carbene; palladium complex; synthetic method